PENGARUH EXPOSURE MEDIA SOSIAL INSTAGRAM TERHADAP MINAT PENGGUNA JASA TRANSPORTASI UDARA UNTUK MELAKUKAN PENERBANGAN DI BANDAR UDARA INTERNASIONAL YOGYAKARTA - Noor Afni Purnamasari; Herida Panji Olivia Azhar (Pusat Riset dan Inovasi Nasional, 2023)
The airport is one of the most important facilities. The airport is not only a supporting facility for air transportation for aircraft to land and take off, but the airport is also a symbol as well as a gateway to an area and even a regional icon that is very proud of for the region. Exposure or exposure to social media is a gift of popularity by someone who has great influence, such as an influencer. Usually this is done by creating content and then uploading it to social media such as Instagram, or other social media platforms and exposure is also known as ad space. In essence, interest is someone's desire or someone's intention to do something, so that in the service user's interest is someone's desire or intention to use a service. This study uses a quantitative descriptive method. The number of samples in this study were 100 respondents. Data collection techniques were by giving questionnaires to respondents, interviews and documentation. In proving and analyzing this, validity and reliability tests, simple linear regression tests, and the coefficient of determination are used. Based on the hypothesis and analysis carried out in this study, namely regarding the effect of Instagram social media exposure on the interest of service users, it can be seen for the Instagram social media exposure variable for a constant value of 31.940 and for the dependent variable the interest of air transportation service users for the regression coefficient of 0.603 where each the addition of 1% in the value of the